Micropropagation of valuable walnut genotypes for timber production: new advances and insights - Ricardo Julian Licea-Moreno; Alexandru Fira; Georgi Chocov (Annals of Silvicultural Research, 2020)
The intensive production of timber from walnuts is mainly hampered by the scarcity of varieties for this purpose. While the hybrid progeny Mj209xRa is considered suitable for timber production in Europe, problems associated with its recalcitrance, the low ability for rooting and the high mortality of acclimated vitroplants, limit the reproduction of elite trees. This research was aimed to assess the influence of two methods for the in vitro introduction of several walnut genotypes, to determine the effects of temporary immersion systems (TIS) on proliferation and rooting, and to reduce the random losses of acclimated vitroplants. Hence, trees from Mj209xRa progeny as well as some common walnuts were used. As an outstanding result, the in vitro establishment of 6 out of 7 trees was obtained. Also important was the improving of quality of microshoots, the multiplication ratios and the rooting using TIS through the management of the kind of bioreactor, the volume of culture media, and the kind of explant inoculated. The direct transplant to field nursery of acclimated vitroplants considerably increased their quality, while mortality was highly reduced. Certainly, these results represent a great contribution to the current micropropagation protocol, especially with the potential introduction of TIS for massive plant production